2008
DOI: 10.1111/j.1872-034x.2007.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus infection as a risk factor for hepatocellular carcinoma in patients with chronic hepatitis C in whom viral eradication fails

Abstract: Occult HBV was a risk factor for HCC development in patients with chronic hepatitis C in whom HCV eradication had failed. Therefore, patients with chronic hepatitis C with occult HBV should be monitored carefully for HCC after IFN therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 33 publications
3
53
0
Order By: Relevance
“…In follow-up periods of 82.8 ± 32.6 months, eight out of nine patients who acquired HCC were OHB positive at the time of final follow-up (73). In a similar finding, in a period of 91.8 ± 48.5 months, four out of eight OHB positive cases had acquired HCC (72). However, one follow-up study found a negative correlation (74); specifically, only one of seven OHB and HCV co-infected patients whose HCV was not without HCV eradicated ion with interferon therapy developed HCC during average periods of 58.6 ± 18.1 months.…”
Section: Hepatocellular Carcinoma (Hcc)supporting
confidence: 68%
See 1 more Smart Citation
“…In follow-up periods of 82.8 ± 32.6 months, eight out of nine patients who acquired HCC were OHB positive at the time of final follow-up (73). In a similar finding, in a period of 91.8 ± 48.5 months, four out of eight OHB positive cases had acquired HCC (72). However, one follow-up study found a negative correlation (74); specifically, only one of seven OHB and HCV co-infected patients whose HCV was not without HCV eradicated ion with interferon therapy developed HCC during average periods of 58.6 ± 18.1 months.…”
Section: Hepatocellular Carcinoma (Hcc)supporting
confidence: 68%
“…Three longitudinal follow-up studies showed the role of OHB in HCC development (65,72,73). In follow-up periods of 82.8 ± 32.6 months, eight out of nine patients who acquired HCC were OHB positive at the time of final follow-up (73).…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Some studies have shown that there is no correlation between clinical outcomes and the severity of liver disease and silent HBV infection. However, others have considered that its occurrence plays a role in the severity of histological changes, the development of hepatocellular carcinoma, and a worse response to antiviral treatment in chronic HCVinfected patients [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…Different factors might be associated with the occult course of hepatitis B infection: elapsed time and recovery from infection as a result of host immune response, low viral load, differences in sensitivity of the HBsAg and anti-HBc immunoassays, as well as variability of the HBV genome, and/or the formation of immune-complexes. [27][28][29][30] OBI may impact in several different clinical contexts, including the possible transmission of the infection, the risk of reactivation, the contribution to liver disease progression and to the development of hepatocellular carcinoma. 31 Even though, there is evidence suggesting that in OBI cases, those with anti-HBs are unlikely to be infectious while those with anti-HBc alone may be infectious.…”
Section: Discussionmentioning
confidence: 99%